Learning the Book of Ihya’ ‘Ulum Ad-Din through Anjangsana: Andragogy Practices in a Rotating Arabic Literacy Forum in Situbondo - Abdi, Efan Chairul; Muassomah, Muassomah; Halimi, Halimi; Asy’arie, Bima Fandi; Naknawa, Dulyawit (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study aims to explore the practice of learning to read Arabic texts in the book Iḥyā Ulum ad-Dīn, which then identifies the social role patterns formed within it, and analyzes the principles of andragogy in adult education as reflected through the Anjangsana forum. This study uses an ethnographic approach following a 12-stage developmental research. Data were collected through participant observation during 24 meetings, in-depth interviews with 20 informants, and documentation in the form of recordings, texts from various print media, and digital communication archives. The results indicate that the practice of learning to read Arabic texts during the visit of Iḥyā’ ‘Ulūm ad-Dīn took place through collective sorogan reading by middle-aged and elderly congregants, interpretation of nahwu-ṣarfiyah with typical Islamic symbols, provision of murod in local languages, interactive discussions, and verification of textual variations across printed editions. Learning through the Anjangsana forum exhibits transformative characteristics that can be understood as a form of community of practice. This study offers an alternative, participatory, inclusive, and reflective learning process rooted in local tradition, combining linguistic, spiritual, and socio-religious dimensions.